2019
DOI: 10.1139/bcb-2018-0256
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control of protein synthesis, glucose metabolism, and apoptosis in the brain of hibernating thirteen-lined ground squirrels

Abstract: Thirteen-lined ground squirrels (Ictidomys tridecemlineatus) are excellent models for studying acute brain ischemia because they show high resistance to reductions in blood flow and oxygen delivery without evidence of neurological damage. In this study, we analyzed the insulin signaling pathway and regulation of mitochondrial substrate oxidation in three regions of ground squirrel brain (forebrain, cerebellum, and brainstem), comparing summer, late torpor, and interbout arousal conditions. We found select decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…To be adaptable to environmental changes, these hibernating animals radically reduce their metabolic rates (including body temperature, oxygen consumption, and heart rate) and swiftly convert the primary fuel from carbohydrate to lipid (Chazarin et al, 2019). Through omics analysis, previous studies in the greater horseshoe bat (Rhinolophus ferrumequinum) (Xiao et al, 2019), American black bear (Ursus americanus) (Srivastava et al, 2019), and thirteen-lined ground squirrel (Ictidomys tridecemlineatus) (Tessier et al, 2019) have revealed metabolic depression and shifts in metabolic fuel use during hibernation. In our previous studies (Huang et al, 2019(Huang et al, , 2021, RNA-Seq analysis in the liver of Pelodiscus sinensis between nonhibernation and hibernation periods indicated that genes involved in lipid β-oxidation were up-regulated, while genes responsible for carbohydrate catabolism were down-regulated during hibernation.…”
Section: Discussionmentioning
confidence: 99%
“…To be adaptable to environmental changes, these hibernating animals radically reduce their metabolic rates (including body temperature, oxygen consumption, and heart rate) and swiftly convert the primary fuel from carbohydrate to lipid (Chazarin et al, 2019). Through omics analysis, previous studies in the greater horseshoe bat (Rhinolophus ferrumequinum) (Xiao et al, 2019), American black bear (Ursus americanus) (Srivastava et al, 2019), and thirteen-lined ground squirrel (Ictidomys tridecemlineatus) (Tessier et al, 2019) have revealed metabolic depression and shifts in metabolic fuel use during hibernation. In our previous studies (Huang et al, 2019(Huang et al, , 2021, RNA-Seq analysis in the liver of Pelodiscus sinensis between nonhibernation and hibernation periods indicated that genes involved in lipid β-oxidation were up-regulated, while genes responsible for carbohydrate catabolism were down-regulated during hibernation.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic and transcriptomic investigations have comprehensively catalogued the impact of season, torpor, and hibernation on cellular and metabolic pathways in several different tissues of hibernating ground squirrels, including the brain (6,(10)(11)(12)(13)(14)(15)(16). Although the mechanisms underlying hibernating ground squirrel ischemia and hypothermia tolerance in the brain are not fully elucidated, studies suggest that post-translational modifications, regulation of cytoskeletal proteins, and upregulation of antioxidants play a prominent role (17)(18)(19). Gene expression profiling and bioinformatic analyses also indicate the cytoprotective contributions of mitochondrial and lysosomal pathways in adapting to hypothermia and hypoxia in ground squirrel and marmot species (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic and transcriptomic investigations have comprehensively catalogued the impact of season, torpor, and hibernation on cellular and metabolic pathways in several different tissues of hibernating ground squirrels, including brain (6, 10-16). Although the mechanisms underlying hibernating ground squirrel ischemia and hypothermia tolerance in the brain are not fully elucidated, studies suggest that post-translational modifications, regulation of cytoskeletal proteins, and upregulation of antioxidants play a prominent role (17-19). Recent studies employing unbiased next-generation sequencing and bioinformatics approaches have also highlighted the cytoprotective contributions of mitochondrial and lysosomal pathways in adapting to hypothermia and hypoxia in ground squirrel and marmot species (20, 21).…”
Section: Introductionmentioning
confidence: 99%